The Impact of Service Quality and Price Fairness on Repurchase Intention Through Customer Satisfaction: A Study of Natasha Skin Care Clinic Customers in DKI Jakarta - Gulo, Eirene Nifati Pangkey; Sabar, Mudji (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes how service quality, price fairness affects customer satisfaction and repurchase at Natasha Skin Care. The aim of this research is to explore the influence of service quality and price fairness on repurchase intentions, with customer satisfaction as a mediating variable. It is hoped that the findings from this research will help Natasha Skin Care formulate a more effective strategy to increase customer loyalty amidst intense competition. In this research, a nonprobability sampling method was used with a purposive sampling technique. This technique is based on certain considerations that are relevant to the research objectives. In this research, the number of samples collected was 150. Data collection was carried out using primary data obtained directly through the process of interviews, observations and distribution of questionnaires and secondary data obtained from existing sources, not through direct collection by researchers. Testing the measurement model uses a validity test consisting of convergent validity, Average Variance Extracted (AVE), and Discriminant Validity and a reliability test carried out by measuring Cronbach's Alpha and Composite Reliability values. Structural Model Testing (Inner Model) The evaluation stage of the inner model structural model is carried out by analyzing the R-Square value. The research results show that service quality significantly increases customer satisfaction and encourages repurchase intention, while price fairness also has a positive impact on satisfaction and repurchase intention. Ultimately, customer satisfaction serves as the main mediator in the relationship between service quality, price fairness, and repurchase intention.